Participants' experiences of the management of screen‐detected complex polyps within a structured bowel cancer screening programme - Lenira Semedo; Ardiana Gjini; Sunil Dolwani; Kate J. Lifford (Wiley, 2022)
Abstract Background The Bowel Screening Wales complex polyp removal service was introduced to address variations in surgery rates for screen‐detected complex benign colorectal polyps, to improve the quality of the screening service and to make management of these polyps more equitable across Wales. Little is known about patient experiences and the potential impact on quality of life when undergoing complex polyp removal. This study is part of a wider research programme evaluating the decision‐making, pathways and outcomes from complex polyp removal. Objective This study aimed to understand experiences of having a complex polyp removed and how this may influence quality of life. Design Semi‐structured telephone interviews were conducted, and a thematic approach was used for data analysis. Setting and Participants All participants had a complex polyp removed after a positive stool test and review by Bowel Screening Wales' Network Multi‐Disciplinary Team. Results Twenty‐one participants were interviewed. Most participants had their complex polyps removed endoscopically and reported no or minor problems or negative outcomes following their procedure. For a small minority, worse problems (e.g., pain, bowel dysfunction) and negative outcomes (e.g., cancer) followed their procedures. Most participants felt supported and reassured throughout their procedures. Any physical and emotional changes to quality of life were mainly linked to procedure outcomes. Discussion Experiences of complex polyp removal were generally positive, with minimal changes in quality of life. Conclusions While most people had a positive experience of having a complex polyp removed, support initiatives, such as counselling or signposting to coping strategies, may be helpful to reduce any potential negative effects of procedures on quality of life. Patient or Public Contribution Four patient and public involvement partners provided feedback on participant materials.